What makes you watch it when you can play it?: the evolution of gaming streaming and the motivational factors concerning viewership - Rato, João Paulo Casimiro da Costa Amaral (2021)
Gaming streaming has been increasing vastly throughout this decade, having a total of 1.9 billion hours of video on TwitchTv in August alone, reflecting a 27% year- over-year growth (Gamesindustry, 2021). This dissertation’s primary objective is to quantify the motivational relevance that a Portuguese viewer has concerning gaming streaming content in the online platform denominated TwitchTv, additionally addressing the evolution of streaming and gaming. A questionnaire was created and shared on a multitude of social media platforms in order to gather data to analyze it via a dedicated software. An analysis was used in order to test the validity of the research hypothesis, being it One Sample Student’s T-Test. With this research, the purpose was to identify which of the user needs posed a positive effect regarding the usage of TwitchTv. The main conclusions were that the affective need has a positive effect in TwitchTv usage, while there’s no evidence to support other needs having a positive effect concerning TwitchTv usage. Concerning future research, this dissertation addresses the interest of expanding the scope of research to not only TwitchTv as a streaming platform but to other online networks, due to the suitable approach of User and Gratifications theory.